Revisiting immunology textbooks: Considering potential insights based on the role of RNA-guided antiviral defense - Muratkhodjaev, Javdat; Muratkhodjaeva, Saodat; Aripova, Tamara (Trends in Immunotherapy, 2024)
Amidst the COVID-19 pandemic, this article offers a cautious re-evaluation of traditional notions surrounding the immune system’s role in combating viral infections. Departing from the prevalent emphasis on antibodies and T cells, the manuscript proposes a hypothesis highlighting the pivotal role of RNA interference present in every nucleated cell of the human body for antiviral defense. This system, honed over years of co-evolution with viruses, harbors a diverse array of microRNAs aimed at suppressing viral replication. Additionally, in the event of failure, novel microRNAs are synthesized to target specific viruses, underscoring the concept of natural immunity and RNA interference’s adaptability. Delving into the sentinel role of the specialized immune system (SIS), the article underscores its significance in safeguarding the body’s integrity and combating tumors, extending beyond mere adaptation to pathogens. It also discusses the risks associated with antibody-dependent enhancement of infection and the depletion of naive T and B cells resulting from extensive use of antiviral vaccines. By accentuating the significance of RNA interference as an often-overlooked aspect of human antiviral defenses, the authors advocate for broader, more exploratory discussions within the scientific community regarding the intricate nature of immune responses and vaccine efficacy.